Does ICT-based aquaculture extension contribute to greater adoption of good management practices and improved incomes? Evidence from Ghana - Ntiri, Prosper; Ragasa, Catherine; Anang, Samuel Afotey; Kuwornu, John K. M.; Torbi, Eva Nimorme (Elsevier, 2022)
This paper aims to assess the coverage and contribution of different information and communication technology (ICT) tools (mobile phone, WhatsApp platform, television, and radio) in the dissemination of aquaculture and market information to fish farmers in Ghana. Data from a 2021 survey of 391 active fish farmers were analyzed using propensity score matching, inverse probability weighted regression adjustment, and multivariate probit regression models. Mobile phone (phone-based app, internet search, or social media) is the most used ICT tool for aquaculture advice, followed by television programs. Results show that receiving aquaculture information through ICT tools has a positive and significant average treatment effect on the adoption of good management practices, farm productivity, and farmers' income. Farmers receiving aquaculture information from mobile phone and television programs had higher adoption of good practices, production, and income on average. Farmers receiving aquaculture information from both ICT tools and extension agents achieved the highest harvest and income on average. Results also show that the adoption of the various ICT tools is interrelated, whereas several factors—including age, education, farming experience, share of fish farming in household income, and extension contact—influence the choice of ICT tool. Mobile-based extension was more accessible to youth and more educated farmers, and it could be a good medium for reaching these groups. Television and radio programs are accessible to all types of farmers from different backgrounds; these media are currently underutilized for aquaculture promotion and their application could be enhanced and expanded for current and future projects.